The acoustics of uvulars in Tlingit - Denzer-King, Ryan (No Publisher Supplied, 2013)
This paper looks at the acoustics of uvulars in Tlingit, an Athabaskan language spoken in Alaska and Canada. Data from five native speakers was used for acoustic analysis for tokens from five phoneme groups (alveolars, plain velars, labialized velars, plain uvulars, and labialized uvulars). The tokens were analyzed by computing spectral moments of plosive bursts and fricatives, and F2 and F3 values for post-consonantal vowels, which were used to calculate locus equations, a descriptive measure of the relationship between F2 at vowel onset and midpoint. Several trends were observed, including a greater difference between F2 and F3 after uvulars than after velars, as well as a higher center of gravity (COG) and lower skew and kurtosis for uvulars than for velars. The comparison of plain versus labialized consonants supports the finding of Suh (2008) that labialization lowers mean burst energy, or COG, and additionally found labialization to raise skew and kurtosis.